INTEGRASI FONOLOGI BAHASA MINANGKABAU DALAM BAHASA MELAYU BENGKULU - NFN Syamsurizal (Balai Bahasa Kalimantan Barat, 2019)
This paper aims to describe the integration of the phonology of the Minangkabau language in the Bengkulu Malay language in sociolinguistic perceptions. The method used in this research is descriptive method. Data were collected using the listening method, with the basic techniques in the form of tapping techniques, free engages involved in competent listening and note taking techniques. The listening is done by tapping into the use of language in the